Projecting Stratocumulus Transitions on the Albedo—Cloud Fraction Relationship Reveals Linearity of Albedo to Droplet Concentrations. Issue 20 (13th October 2022) - Goren, Tom; Feingold, Graham; Gryspeerdt, Edward; Kazil, Jan; Kretzschmar, Jan; Jia, Hailing; Quaas, Johannes
Abstract: Satellite images show solid marine stratocumulus cloud decks (Sc) that break up over the remote oceans. The Sc breakup is initiated by precipitation and is accompanied by a strong reduction in the cloud radiative effect. Aerosol has been shown to delay the Sc breakup by postponing the onset of precipitation, however its climatic effect is uncertain. Here we introduce a new approach that allows us to re‐cast currently observed cloud cover and albedo to their counterfactual cleaner world, enabling the first estimate of the radiative effect due to delayed cloud breakup. Using simple radiative approximation, the radiative forcing with respect to pre‐industrial times due to delayed Sc breakup is −0.39 W m −2 . The radiative effect changes nearly linearly with aerosol due to the droplet concentration control on the cloud cover, suggesting a potentially accelerated warming if the current trend of reduction in aerosol emissions continues. Plain Language Summary: The response of cloud cover to aerosol is a climatologically important quantity that has been extremely difficult to estimate. The challenge is that one would need to estimate the fractional area that is currently overcast, but which would have been partly overcast in a cleaner atmosphere. Global climate models (GCMs) are one tool to address such a problem. They allow one to change aerosol levels and to evaluate the cloud response. However, representation of warm, low‐level cloud processes, and in particular aerosol‐cloud interactions in GCMs, is inadequate. Here we introduce an observational method that allows us to re‐cast the currently observed cloud cover and albedo of oceanic warm clouds to their counterfactual state in a cleaner world. We find a linear relationship between the cloud radiative effect and droplet concentration. If we continue to experience a decrease in aerosol emissions then we anticipate a reduction in the aerosol‐cloud radiative effect. The global annual radiative forcing associated with anthropogenic aerosol delaying closed cell breakup is found to be −0.39 W m −2 . Key Points: A simple model is presented to describe closed cell breakup by initiation of precipitation The model demonstrates that the global annual radiative effect due to delayed closed cells breakup changes nearly linearly with emissions The linearity emerges from the nearly linear relationship between cloud cover and albedo